Deterministic placement of ultra-bright near-infrared color centers in arrays of silicon carbide micropillars - Castelletto, Stefania (Beilstein J Nanotechnol, 2019)
We report the enhancement of the optical emission between 850 and 1400 nm of an ensemble of silicon mono-vacancies (V(Si)), silicon and carbon divacancies (V(C)V(Si)), and nitrogen vacancies (N(C)V(Si)) in an n-type 4H-SiC array of micropillars. The micropillars have a length of ca. 4.5 μm and a diameter of ca. 740 nm, and were implanted with H(+) ions to produce an ensemble of color centers at a depth of approximately 2 μm. The samples were in part annealed at different temperatures (750 and 900 °C) to selectively produce distinct color centers. For all these color centers we saw an enhancement of the photostable fluorescence emission of at least a factor of 6 using micro-photoluminescence systems. Using custom confocal microscopy setups, we characterized the emission of V(Si) measuring an enhancement by up to a factor of 20, and of N(C)V(Si) with an enhancement up to a factor of 7. The experimental results are supported by finite element method simulations. Our study provides the pathway for device design and fabrication with an integrated ultra-bright ensemble of V(Si) and N(C)V(Si) for in vivo imaging and sensing in the infrared.